A novel control strategy: Suppressing histone acetyltransferase ClHAC703 with curcumin to prevent germination of the invasive weed Cenchrus longispinus - Xiao-Min Han; Jia-Ying Wang; Yan-Ping Fu; Bin Guo; Wei He; Ya-Hui Wei (Plant Science, 2026)

The Holocene transgression in the Bohai Sea: insights from multi-proxy sedimentary records - Lichao Tang; Ya Ping Wang; Yuanfu Yue; Wei Feng; Fu Wang; Cong-Qiang Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Understanding variation in sustainable development goal relationships across spatial scales matters for making consistent priorities - Kai Wu; Junze Zhang; Prajal Pradhan; Cameron Allen; Min Cao; Jian Lin; Zhongchang Sun; Zheng Hu; Ya Tian; Guonian Lü; Huadong Guo; Bojie Fu; et al. (Sustainable Production and Consumption, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Low-dose arsenate promotes high-efficiency anammox: From granular properties to synergistic metabolism - Que Wang; Xiao-Wei Xu; Zhang-Yi Wang; Hong-Yuan Liu; Lei Wang; Hui-Ming Fu; Ya-Min Liu; Peng Yan; Ling-Ling Wang; You-Peng Chen (Chemical Engineering Journal, 2026)

D–A–A engineered covalent organic frameworks for photocatalytic degradation of microcystin-LR and inactivation of Microcystis aeruginosa - Niao Fu; Qingzhi Liu; Ya Zou; Yujiao Liu; Anzhong Peng; Vadim Popkov; Junfeng Li; Kezhen Qi; Jieli He (Chemical Engineering Journal, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Self-crosslinking emulsion gels stabilized by thiolated pectin for high-efficiency curcumin encapsulation: A crosslinker-free strategy - Lv Ya-Nan; Wang Ping-Ping; Fu Xiong; Chen Chun (Food Chemistry, 2026)

A coupled elastoplastic damage subloading surface model for rock-like geomaterials subjected to triaxial cyclic compression - Jun Wu; Wei Wang; Ya-jun Cao; Shi-fan Liu; Wan-qing Shen; Jian-fu Shao (Computers and Geotechnics, 2026)

Developmental toxicity and thyroid hormone receptor antagonism of chlorothalonil in zebrafish: insights from transcriptomics and in vitro assays - Ya Liu; Jingjing Miao; Hui Fu; Yuxin Wen; Luqing Pan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

CRISPR-Cas12a-coupled split-promoter activator bridge enables reusable one-reporter-multiple-target cell-free nucleic acid diagnostics - Fengling Fang; Mingming Zhao; Weiquan You; Xiangjun Tang; Shanjian Chen; Yao Yin; Qishui Ou; Yueguo Li; Ya Fu (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Hydrologic response of slopes to rainfall patterns under variable bedrock topography - Jyun-Kai Yang; Ya-Sin Yang; Hsin-Fu Yeh (Journal of Earth System Science, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

An optimality method to quantify ecosystem-level soil moisture deficits responses via photosynthesis-hydraulics coordination - Lijiang Fu; Jinglu Tan; Vladimir Lysenko; Qian Xia; Ya Guo (Ecohydrology & Hydrobiology, 2026)

Genome-Wide Identification of 33 Drought-Responsive P450 Genes in Sorghum Bicolor and Analyses of their Tissue-Specific Expression Under Abiotic Stress Conditions - Senjie Fu; Junxia Li; Na Qin; Ya Jing; Cancan Zhu; Shutao Dai; Chengyang Zhang; Chunyi Wang (Tropical Plant Biology, 2026)

A novel C17-sesquiterpene alkaloid derived from Dendrobium huoshanense : in vitro evaluation of its anti-lung cancer activity and molecular dynamics simulation study - Jun Chen; Xiu-Mei Li; Yong-Peng Sun; Ya-Feng Dai; Shi-Hao Li; Nai-Fu Chen; Nai-Dong Chen (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Amoxicillin and copper affect humification during compost: Insight into dissolved organic matter and bacterial community succession - Ya Su; Qianting Zhuo; Pingfan Wu; Haochen Shao; Shanfei Fu; Guangqun Huang (Environmental Research, 2026)

VHL Suppresses Angiogenesis Through HIF-1a-Mediated Ang/Tie2/AMPK/VEGF Signaling Pathway in Tie-2 Expressed Macrophages (TEMs) - Min-Cheng Zou; Yu-Hao Yang; Yun-Peng Mao; Ya Liu; Hui-Bing Gao; Wen-Dong Liu; Jia Liu; Fu-Yong Zhang (Biochemical Genetics, 2026)

Oxime ester–linked N-phenylphthalimide derivatives as PPO inhibitors: structure–activity relationships, herbicidal activity, crop selectivity, and in silico safety assessment - Xian-Ming Zhang; Yue-Li Zou; Ya Jiang; Si-Yi Yao; Shuang Gao; Li-Xia Zhao; Yu-Long Liu; Ying Fu (Pesticide Biochemistry and Physiology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Potential role of AHL-mediated quorum sensing in filamentous bulking induced by Sphaerotilus natans in the activated sludge process with low dissolved oxygen - Yi Fu; Wei-Xin Liu; Shao-Yang Liu; You-Peng Chen; Song-Ya Li; Fang Fang; Jin-Song Guo; Peng Yan (Journal of Environmental Chemical Engineering, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Harnessing Machine learning to quantify ecosystem services in coastal Wetlands: A case study of the Bohai economic Rim - Ting Lu; Ya Ping Wang; Jiyuan Jin; Shibing Zhu; Jianhua Gao; Hu Ding; Qinglong Wu; Fu Wang; Chao Gao (Ecosystem Services, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Antifouling compounds from marine fungus Aspergillus iizukae GXIMD 00548 - Chun-Qing Fu; Meng-Fan Qi; Chun-Xiao Chen; Hua-Qing Huang; Xiao-Wei Luo; Cheng-Hai Gao; Yong-Hong Liu; Xin-Ya Xu (Biofouling, 2026)

Valorization and detoxification of MSWI fly ash via carbonation-ultrasonication for a low-chlorine, high-calcium, and low-toxicity derivative - Xuyang He; Dingyuan Zhang; Jincheng Wang; Weihua Li; Xue Li; Yingjie Sun; Qingjian Zhang; Ying Zhu; Rongxing Bian; Weichen Xu; Xuexin Fu; Ya-nan Wang; et al. (Journal of Cleaner Production, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Exploring the impacts of flavonoid compounds on escitalopram metabolism: a combined in vitro and in vivo study - Hailun Xia; Jun Wu; Haoxin Fu; Peiqi Wang; Ruibin Li; Lu Cao; Ya-nan Liu; Lu Shi; Ren-ai Xu (Molecular Diversity, 2026)

Leaching behavior and mechanisms of PCDD/Fs from solidified/stabilized fly ash under landfill leachate and alkali washing conditions: Inspired by co-landfilling with MSW - Xue Li; Yingjie Sun; Weihua Li; Qingjian Zhang; Yanqi Nie; Dong Liu; Weichen Xu; Xuexin Fu; Rongxing Bian; Huawei Wang; Ya-nan Wang (Waste Management, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Recombinant GnRH6-kisspeptin-CRM197 vaccine inhibits reproductive function in male rats and dogs - Yanyun Zhu; Mengxian Li; Xiangyang Jiang; Dongyuan Fu; Zhihao Pan; Zhuoya Wu; Kejian Han; Ya Liu; Yunsheng Li; Tong Yu; Kaiyuan Ji; Mengling Peng; et al. (The Veterinary Journal, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Study on the effects of representative spice polyphenols on the in vitro digestive properties of tilapia myofibrillar protein and its mechanism of action: based on physical and chemical properties and enzyme activity - Zirui Fu; Jun Li; Ya Wei; Jianwei Cen; Huan Xiang; Xiao Hu; Chunsheng Li; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Hui Huang; Shuxian Hao (Food Chemistry, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Disentangling the relative effects of solar radiation and vapor pressure deficit on ecosystem photosynthetic efficiency based on global eddy-covariance observations - Lijiang Fu; Jinglu Tan; Vladimir Lysenko; Ya Guo (Plant Ecology, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Enhancing Laterite’s Mechanical Properties and Reducing Water Sensitivity with Glycerol Monostearate - Kun-Yu Fu; Yan-Ge Chen; Ying-Zhen Ji; Qi-Ya Wang (Geotechnical and Geological Engineering, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Synthesized capric-lauric acid structural lipids improve metabolic health in obesity: roles of antimicrobial activity, systemic inflammation and gut microbiota remodeling - Mengyu Yang; Xiyu Fu; Shiyuan Liu; Ya Pan; Haiying Cai; Jing Wang; Fengqin Feng; Minjie Zhao (Food Bioscience, 2025)

Morphology of the subgenital plate gland in Solenopsis males (Hymenoptera, Formicidae) - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Johan Billen (Arthropod Structure & Development, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Full-field apparent resistivity definition of ground-airborne transient electromagnetic based on differential pulse - Ya'nan Fan; Xiu Li; Kailiang Lu; Juanjuan Li; Tianchi Fu; Xiaozhao Li (Journal of Applied Geophysics, 2025)

Corrigendum to “Effect of the glycosylation of tilapia proteins on the simulated in vitro digestive properties in the elderly” [Food Bioscience, 68, June (2025), 106702] - Zirui Fu; Huan Xiang; Shuxian Hao; Ya Wei; Xiao Hu; Yongqiang Zhao; Yanyan Wu; Shengjun Chen; Hui Huang; Jianwei Cen (Food Bioscience, 2025)

High co-infection burden and ICU-specific pathogen profiles in pediatric Candida albicans respiratory infections: a large-scale tNGS analysis - Ya Huang; Huideng Zhou; Jiangyang Zhao; Lishai Mo; Junming Lu; Guangbing Liu; Shuo Zhang; Yanhua Feng; Wenting Tang; Qiang Huang; Yan Chen; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The biocontrol effect and mechanism of the marine-derived fungus Epicoccum nigrum against Alternaria alternata, the causal agent of tomato black spot disease - Si-Qi Fu; Fei Cao; Sen Pang; Xiao-Qian Qi; Zhi-Hong Xu; Ya-Hui Zhang; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu (Pesticide Biochemistry and Physiology, 2025)

Adsorption and coarsening of gold nanoparticles in iron (oxyhydr)oxides lead to high-grade gold mineralization - Feng-Xia Huang; Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Xin-Fu Zhao; Yong Wei; Wei Feng; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2025)

ZnO/LIG nanocomposites to detect acetone gas at room temperature with high sensitivity and low detection limit - Li Yang; Wenyuan Fu; Ya Wang; Zhida Wang; Longbiao Mao; Luxiang Xu; Chengpeng Yao; Hongyu Zhang; Sisi Chen; Hui Zhang; Huanyu Cheng (Chemical Engineering Journal, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

Carnosic Acid Attenuated the Motor Impairment by Bisphenol A is Related to the Regulation of Autophagy Through Parkin in In Vitro and In Vivo - Chun-Huei Liao; Ya-Chen Shih; Hsi-Yun Huang; Jing-Wei Chen; Shao-I Hsu; Chiao-Ni Lai; Ru-Huei Fu; Chia-Wen Tsai (Molecular Neurobiology, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

The Role of Complement C1qa in Experimental Intracerebral Hemorrhage - Xiongjie Fu; Fenghui Ye; Yingfeng Wan; Guohua Xi; Ya Hua; Richard F. Keep (Translational Stroke Research, 2025)

Glutathione's role in mitigating cadmium stress in Pogostemon cablin: Insights from combined transcriptomic and metabolomic approaches - Zhineng Fu; Yanqiang Yao; Muhammad Zeeshan Ul Haq; Ya Liu; Dongmei Yang; Huageng Yang; Yougen Wu (Journal of Hazardous Materials, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Bioinspired hydrogel tactile sensor via pressure-intensified ion signals with self-healing and anti-frozen capability - Yi-Han Xue; Tian-Run Lv; Huiting Zhang; Ya-Qiong Yang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2025)

Clinical characteristics and co-infection analysis of influenza a virus in pediatric respiratory infections: a study based on tNGS technology - Chunyun Fu; Qiang Huang; Jiangyang Zhao; Lishai Mo; Wenting Tang; Junming Lu; Yili Zhang; Xiangjun Lu; Ya Huang; Yanhua Feng; Xuehua Hu; Yanqing Tang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Effect of the glycosylation of tilapia proteins on the simulated in vitro digestive properties in the elderly - Zirui Fu; Huan Xiang; Shuxian Hao; Ya Wei; Xiao Hu; Yongqiang Zhao; Yanyan Wu; Shengjun Chen; Hui Huang; Jianwei Cen (Food Bioscience, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Sternal glands in Strumigenys ants - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Johan Billen (Arthropod Structure & Development, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Clinical and prognostic insights into Chlamydia trachomatis in pediatric acute respiratory infections: evidence from targeted next-generation sequencing of 5,021 cases - Chunyun Fu; Huan Zhang; Xiangjun Lu; Yanhua Feng; Lishai Mo; Junming Lu; Huiping Huang; Qiang Huang; Cuihong Lu; Wenting Tang; Ruting Chen; Silin Jiang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

MPI ‐ ESM Grand Ensemble‐Simulated Influence of the Mount Pinatubo Volcanic Eruption on Winter Climate Over the Mid‐to High‐Latitude Northern Hemisphere Continents - Zongjin Qin; Tao Wang; Ya Gao; Yuanhai Fu (International Journal of Climatology, 2025)
In this study, the effects of the Mount Pinatubo eruption on surface air temperature (SAT) over mid‐ to high‐latitude Northern Hemisphere (NH) continents in December–January–February (DJF) 1991/92 were investigated using MPI‐ESM Grand Ensemble simulations, observations and reanalysis data. The results indicated that the 1991 Mount Pinatubo eruption was not the primary cause of the SAT warming anomaly over the mid‐ to high‐latitude NH continents in DJF 1991/92. In the observations, a positive Arctic Oscillation (AO) or North Atlantic Oscillation (NAO)‐like pattern dominated the warming of Eurasia, while a Pacific North American (PNA)‐like pattern dominated the warming of North America. However, the model ensemble mean (MEM) simulated SAT and sea level pressure anomalies were much weaker over high‐latitude continents. Furthermore, by categorising the 100 MPI‐ESM Grand Ensemble simulations into four categories, we found that the probability of warm and cold temperature anomalies occurring over Eurasia and North America was nearly equal. Only about 22% of the MPI‐ESM Grand Ensemble members simulated winter warming over the mid‐ to high‐latitude NH continents that matched observations. Our study suggested that this winter warming was mostly caused by the internal variability of the climate system, which was consistent with previous studies. A more detailed analysis indicated that, following the Mount Pinatubo eruption, the intrinsic phase shifts in the AO and PNA remained key factors driving the SAT variations in Eurasia and North America, respectively.

Potential roles of quorum quenching in microbial aggregates during wastewater treatment - Yi Fu; Song-Ya Li; Yang Chen; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Bioresource Technology, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Tidal-driven N2O emission is a stronger resister than CH4 to offset annual carbon sequestration in mangrove ecosystems - Chunwei Fu; Zhibo Shen; Shiheng Tang; Fengying Li; Xin Quan; Yang Wang; Ya Zhuang; Jiasen Zhong; Jianan Liu; Jianzhong Su; Min Xu; Yu Han; et al. (Science of The Total Environment, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Microbial and chemical diversity analysis reveals greater heterogeneity of Liubao tea than ripen Pu-erh tea - Hao-Yi Yan; Meng-Fu Chen; Yi-Chen Hu; Ya-Shuai Kong; Tie-Jun Ling (Food Research International, 2025)

An improved SIF-based GPP estimation method based on quantifying the joint effect of photosynthetically active radiation and temperature on LUE/SIFyield - Lijiang Fu; Junqing Chen; Jinglu Tan; Suleyman I. Allakhverdiev; Ya Guo (Ecological Modelling, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Rigid interface induced structural transformation in Zn, Ni-ZIF for enhanced electromagnetic wave attenuation - Xueting Zhang; Shaocong Zhong; Pianpian Zhang; Anqi Lun; Baoshan Li; Junjie Fu; Xinyu Wang; Ya’nan Yang; Long Xia (Chemical Engineering Journal, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Study on calcium dissolution of concrete specimens with surface cracks - Jian-Hua Jiang; Jia-Bing Zhou; Fu-Liang Ma; Wei Zhang; Ya-Bing Yu (European Journal of Environmental and Civil Engineering, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Vocalization-induced middle ear muscle reflex and auditory fovea do not contribute to the unimpaired auditory sensitivity after intense noise exposure in the CF-FM bat, Hipposideros pratti - Zhongdan Cui; Jianwen Zou; Yuting Zhou; Yuntu Cao; Haonan Song; Haoyue Xu; Jing Wu; Baoling Jin; Lijian Yang; Ya Jia; Qicai Chen; Ziying Fu (Journal of Comparative Physiology A, 2025)

Technical and environmental assessment of sludge-derived slag generated from high temperature slagging co-gasification process as a sustainable construction material - Ya Zhao; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Xiaoxu Fu; Yan Gu; James Oh; Grzegorz Lisak (Waste Management, 2024)

Atmospheric deposition of pollutants at three altitudes on Mount Emei, Sichuan Basin, southwestern China - Zhongjun Xu; Yuhan Fu; Qi Ying; Philip K. Hopke; Xi Shu; Xiaolan Yang; Xue Qiao; Ya Tang (Science of The Total Environment, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Atmospheric Sulfur and Nitrogen Deposition in Five Nature Reserves of Sichuan Basin to Qinghai-Tibetan Plateau Transect Region, Southwestern China - Zhongjun Xu; Xi Shu; Han Yang; Liqiang Fu; Tingting Liu; Zhonglin Xia; Xue Qiao; Ya Tang (Chinese Geographical Science, 2024)

Dual-channel fluorescent probe for detecting SO2 and Hg2+, and dynamic imaging SO2 under Cd2+ in alfalfa (Medicago sativa) - Ya-Qian Wu; Xiang-Yu Wang; Tian-Wen Bai; Ying-Long Fu (Analytica Chimica Acta, 2024)

High-precision analysis of toxic metals in lithium-ion battery materials across various complex media - Tianyu Qi; Xuezhi Yang; Ya Liu; Haonan Wen; Feiyang Liu; Ziqi Yue; Ziyuan Qi; Haiyan Zhang; Jianjie Fu; Qian Liu; Guibin Jiang (Analytica Chimica Acta, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Adsorption mechanism of sodium oleate at hematite/quartz–water interfaces: A quantitative molecular insight - Xinzhuang Fu; Ya Gao; Chuanxi Peng; Haisheng Han; Wei Sun; Tong Yue (Minerals Engineering, 2024)

Heterostructure g-C3N4/Bi2MoO6 PVDF nanofiber composite membrane for the photodegradation of steroid hormone micropollutants - Zhi-Fu Lin; Han-Ya Lin; Ruey-An Doong; Andrea I. Schäfer (Journal of Hazardous Materials, 2024)

Ferrocenedicarboxylate modified Bi-MOF for water decontamination via different advanced oxidation processes: Multifunction, mechanisms and biotoxicity test - Ya Gao; Fei Wang; Jie Tang; Chong-Chen Wang; Xiao-Hong Yi; Yuwei Wei; Guangchi Liu; Peng Wang; Huifen Fu; Chen Zhao; Xuchun Qiu; Shouliang Yi (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

A new species of Eirictis (Mammalia, Carnivora, Mustelidae) from Lower Pleistocene of Yuanmou Basin, Yunnan, China - Arya Farjand; Li-Ya Fu; Qi-Gao Jiangzuo; Zhi-Heng Liu; Jian Wang; Xin-Ying Zhou; Shun-Dong Bi; Li-Hua Wang (Palaeoworld, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Correction: Study on the circadian rhythm and sleep state characteristics of patients with acute cerebral infarction accompanied by sleep-breathing disorders - Lianhui Wang; Xiaodong Yuan; Ya Ou; Jing Xue; Qian Ma; Yongshan Fu; Pingshu Zhang (Sleep and Biological Rhythms, 2024)

Study on the circadian rhythm and sleep state characteristics of patients with acute cerebral infarction accompanied by sleep-breathing disorders - Lianhui Wang; Xiaodong Yuan; Ya Ou; Jing Xue; Qian Ma; Yongshan Fu; Pingshu Zhang (Sleep and Biological Rhythms, 2024)

A methodological review of compound-specific radiocarbon analysis for polycyclic aromatic hydrocarbons in environmental matrices - Yu Fu; Rui Zhang; Shaopeng Rong; Yuling Wu; Ying Wu; Miaolei Ya (Environmental Pollution, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Energy dependence of synchronization mode transitions in the delay-coupled FitzHugh-Nagumo system driven by chaotic activity - Xuening Li; Dong Yu; Lijian Yang; Ziying Fu; Ya Jia (Cognitive Neurodynamics, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Toxic effects of microplastics and nitrite exposure on intestinal histology, digestion, immunity, and microbial community of shrimp Litopenaeus vannamei - Yi-fu Xing; Xuan-yi Zhu; Jian-hua Huang; Yu-xiu Nan; Ya-fei Duan; Jia-song Zhang (Marine Pollution Bulletin, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Assessing shallow slope stability using electrical conductivity data and soil hydraulic characteristics - Ya-Sin Yang; Hsin-Fu Yeh; Chien-Chung Ke; Lun-Wei Wei (Engineering Geology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Predicting land use change around railway stations: An enhanced CA-Markov model - Fei Fu; Xia Jia; Qiuji Zhao; Fangzhou Tian; Dong Wei; Ya Zhao; Yingzi Zhang; Jian Zhang; Xia Hu; Linchuan Yang (Sustainable Cities and Society, 2024)

A quantitative innovation perspective on synergism and selectivity mechanism of mixed collectors in flotation - Ya Gao; Xinzhuang Fu; Sultan Ahmed Khoso; Zujiang Pan; Haisheng Han; Wei Sun; Tong Yue (Minerals Engineering, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Multiple effects of nano-carbon coating on mediating Schottky barrier height, inhibiting Ti3C2 oxidation and elevating photocatalytic activity in BiOBr/carbon-coated Ti3C2/exfoliated bentonite - Linxing Wang; Kun Liu; Tian Fu; Jing Sun; Jingyuan Yan; Ya Hu; Zhangfa Tong; Hanbing Zhang (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Drivers of low-carbon practices in green supply chain management in construction industry: An empirical study in China - Chun Fu; Ya-Qi Liu; Ming Shan (Journal of Cleaner Production, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Nitrogen self-doped chitosan carbon aerogel integrating with CoAl-LDH for ultra-efficient sulfamethoxazole degradation based on PS-AOPs: From batch to continuous process - Manjun Fu; Bo Chai; Xiaohu Zhang; Ya Sun; Guozhi Fan; Guangsen Song (Journal of Environmental Chemical Engineering, 2023)

Degradation of ofloxacin by high-efficiency almond shell-based biochar via peroxymonosulfate activation: A study of the effect of pore structure - Yi-meng Huang; Fu-zhi Huang; Bing-jun Dong; Xiao-qiang Cao; Ya-nan Shang; Xing Xu (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Revolutionizing wound healing: Ultrashort pulse electric fields in seconds for highly aligned extracellular matrix and efficient cell migration - Xiao-Wei Xiang; Hao-Tian Liu; Wei Liu; Ze-Yao Yan; Yu-Lian Zeng; Ya-Jun Wang; Jing Liu; Yu-Chen Chen; Sai-Xi Yu; Cai-Hui Zhu; Xiao-Nan Tao; Chen Wang; et al. (Chemical Engineering Journal, 2023)

Effects of hysteretic soil water characteristic curves on the hydromechanical behaviour - Ya-Sin Yang; Hsin-Fu Yeh (Journal of Earth System Science, 2023)

Exploring electric moped sharing preferences with integrated choice and latent variable approach - Ching-Fu Chen; Chiang Fu; Pei-Ya Siao (Transportation Research Part D: Transport and Environment, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Single and combined effect of tetracycline and polyethylene microplastics on two drought contrasting cultivars of Oryza sativa L. (Rice) under drought stress - Kiran Yasmin Khan; Barkat Ali; Hafiz Usman Ghani; Lijiang Fu; Mohammad Jahid ul Islam Shohag; Shuang Zhang; Xiaoqiang Cui; Qian Xia; Jinglu Tan; Zeshan Ali; Ya Guo (Environmental Toxicology and Pharmacology, 2023)

A drought stress-sensing technique based on wavelet entropy of chlorophyll fluorescence excited with pseudo-random binary sequence - Qian Xia; Hao Tang; Lijiang Fu; Jinglu Tan; Ya Guo (Computers and Electronics in Agriculture, 2023)

Efficient removal mechanism of an electrical conductivity-enhanced constructed wetlands under particle accumulated conditions - Jiajun Wang; Qin Zhang; Ya-nan Zhang; Mingming Fu; Yanli Ding; Xutao Gao; Lanqian Qin; Ronghua Wang; Shaoyuan Bai (Journal of Cleaner Production, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

Converting sludge to slag through a high temperature slagging co-gasification process: An evaluation based on a demonstration trial and life cycle assessment - Xiaoxu Fu; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Wenqian Chen; Ya Zhao; Stephan Heberlein; Yan Gu; James Oh; Grzegorz Lisak (Chemical Engineering Journal, 2023)

Investigating the causes of O3 pollution in the western rim of sichuan basin, southwestern China - Xi Shu; Zhonglin Xia; Qi Ying; Yuhan Fu; Xue Qiao; Ya Tang (Atmospheric Pollution Research, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Peptides-carrageenan-xanthan gum: Printing mechanism and anti-oxidation under in vitro digestion - Jun-qi Zhan; Wen-tao Yu; Jing-jing Fu; Gao-shang Li; Ya-qin Hu; Yue-wen Chen (Food Bioscience, 2023)

Changes of atmospheric metal(loid) deposition from 2017 to 2021 at Mount Emei under China's air pollution control strategy - Yuhan Fu; Ya Tang; Xi Shu; Philip K. Hopke; Lei He; Qi Ying; Zhonglin Xia; Mengjie Lei; Xue Qiao (Atmospheric Environment, 2023)

Airflow Mitigation and Pollutant Purification in an Idealized Urban Street Canyon with Wind Driven Natural Ventilation: Cooperating and Opposing Effects of Roadside Tree Plantings and Non-uniform Building Heights - Yu-Fei Tang; Ya-Bing Wen; Hao Chen; Zhi-Cheng Tan; Yi-He Yao; Fu-Yun Zhao (Sustainable Cities and Society, 2023)

The Na+/H+ antiporter GbSOS1 interacts with SIP5 and regulates salt tolerance in Gossypium barbadense - Fu-Chun Xu; Mei-Juan Wang; Ya-Wei Guo; Jie Song; Wei Gao; Lu Long (Plant Science, 2023)

Ligand-binding properties of chemosensory protein 1 in Callosobruchus chinensis to mung bean volatiles - Qiang Liu; Mao-Zhu Yin; Sai Ma; Nan Gu; Li-Fu Qian; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Fabrication strategies of metal–organic frameworks derivatives for catalytic aqueous pollutants elimination - Fei Wang; Ya Gao; Shan-Shan Liu; Xiao-Hong Yi; Chong-Chen Wang; Huifen Fu (Chemical Engineering Journal, 2023)

Are the altitudinal patterns of plant diversity derived from field surveys consistent with those from empirical integrated methods? - Qing-hua Zhan; Zhi-hao Fu; Ya-dong Zhou; Xue Yan; Qing-feng Wang (Journal of Mountain Science, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Identification and characterization of immune-related microRNAs in hybrid snakehead(Channa maculata♀ × Channa argus♂)after treated by Echinacea purpurea (Linn.) Moench - Xuelian Tang; Jinghua Fu; Ya Yao; Minjun Xu (Fish & Shellfish Immunology, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

The spongiform tissue in Strumigenys ants contains exocrine glands - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Joshua C. Gibson; Sara McGuire; Andrew V. Suarez; Johan Billen (Arthropod Structure & Development, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

First Asian fossil record of Platydictya (Amblystegiaceae) from the lower Miocene and its paleoenvironmental significance - Liyan Guo; Liang Xiao; Ya Li; Xiangchuan Li; Qin Leng; Nan Sun; Junfeng Guo; Chaofeng Fu; Jianan Wang; Deshuang Ji (Frontiers of Earth Science, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Numerical study of the influence of loading rate on fracture mechanism in elastoplastic rock-like materials with a modified phase-field model - Shi-Fan Liu; Wei Wang; Ya-Jun Cao; Hai-Feng Li; Jian-Fu Shao (International Journal of Rock Mechanics and Mining Sciences, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Impact of polystyrene microplastics with combined contamination of norfloxacin and sulfadiazine on Chrysanthemum coronarium L. - Kiran Yasmin Khan; Guanlin Li; Daolin Du; Barkat Ali; Shuang Zhang; Meiying Zhong; Peter Joseph Stoffella; Babar Iqbal; Xiaoqiang Cui; Lijiang Fu; Ya Guo (Environmental Pollution, 2023)

Poly(caffeic acid) as interlayer to enhance nanofiltration performance of polyamide composite membrane - Xiao-lei Wang; Ya-xian Xue; Shu-qian Dong; Qi Wang; Jiang-tao Yu; Hui-cai Wang; Huan Zhang; Wan Wang; Jun-fu Wei (Desalination, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Spatial transcriptome analysis of long non-coding RNAs reveals tissue specificity and functional roles in cancer - Kang Xu; Xiyun Jin; Ya Luo; Haozhe Zou; Dezhong Lv; Liping Wang; Limei Fu; Yangyang Cai; Tingting Shao; Yongsheng Li; Juan Xu (Journal of Zhejiang University-SCIENCE B, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

The association between hearing threshold and urinary personal care and consumer product metabolites in middle-aged and elderly people from the USA - Yan-Peng Fu; Wen-Yu Chen; Li-Qing Guo; Ya-Qiong Zhu; Jia-Sheng Yuan; Yue-Hui Liu (Environmental Science and Pollution Research, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Water adsorption characteristic and its impact on pore structure and methane adsorption of various rank coals - Ming-yi Chen; Xiao-yun Chen; Liang Wang; Fu-chao Tian; Yu-meng Yang; Xue-jie Zhang; Ya-pu Yang (Environmental Science and Pollution Research, 2022)

Using data-limited approaches to assess data-rich Indian Ocean bigeye tuna: Data quantity evaluation and critical information for management implications - Ya’nan Li; Jiangfeng Zhu; Xiaojie Dai; Dan Fu; Yong Chen (Acta Oceanologica Sinica, 2022)

Chemical composition and anti-hepatoma effect of Annona squamosa L. pericarp oil - Ya-Yun Chen; Fu-Qiang Li; Xiao-Li Zhu; Jian-Wei Chen; Xiang Li (Natural Product Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Effects of gibberellin priming on seedling emergence and transcripts involved in mesocotyl elongation in rice under deep direct-seeding conditions - Ya Wang; Yuetao Wang; Ruifang Yang; Fuhua Wang; Jing Fu; Wenbo Yang; Tao Bai; Shengxuan Wang; Haiqing Yin (Journal of Zhejiang University-SCIENCE B, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Two metabolites isolated from endophytic fungus Coniochaeta sp. F-8 in Ageratina adenophora exhibit antioxidative activity and cytotoxicity - Jie Fu; Liwen Hu; Zhen Shi; Wei Sun; Dong Yue; Ya Wang; Xiaoping Ma; Zhihua Ren; Zhicai Zuo; Guangneng Peng; Zhijun Zhong; Junliang Deng; et al. (Natural Product Research, 2021)

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

Study of pollutant accumulation characteristics and microbial community impact at three bioretention facilities - Ya-jiao Li; Heng Fu; Jing-yu Zhang; Zhao-xin Zhang; Jia-ke Li (Environmental Science and Pollution Research, 2021)

Landslide distribution and sliding mode control along the Anninghe fault zone at the eastern edge of the Tibetan Plateau - Hong-fu Zhou; Bin Liu; Fei Ye; Wen-xi Fu; Wen-qing Tang; Ya-dong Qin; Tian Fang (Journal of Mountain Science, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Comparisons of Subjective and Objective Measures of Free-Living Daily Physical Activity and Sedentary Behavior in College Students - Ya-Wen Hsu; Chia-Chang Liu; Yen-Jung Chang; Yi-Ju Tsai; Wan-Chi Tsai; You Fu (Journal of Science in Sport and Exercise, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Characterization of ZmCOLD1, novel GPCR-Type G Protein genes involved in cold stress from Zea mays L. and the evolution analysis with those from other species - Ya-Nan Jin; Zhen-hai Cui; Ke Ma; Jia-Lu Yao; Yan-Ye Ruan; Zhi-Fu Guo (Physiology and Molecular Biology of Plants, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Development of a minimized model structure and a feedback control framework for regulating photosynthetic activities - Lijiang Fu; Govindjee Govindjee; Jinglu Tan; Ya Guo (Photosynthesis Research, 2020)

KIF3A regulates the Wnt/β-catenin pathway via transporting β-catenin during spermatogenesis in Eriocheir sinensis - Ya-Jing Liang; Jia-Hao Ni; Lan-Min Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

An on-demand construction method of disaster scenes for multilevel users - Weilian Li; Jun Zhu; Yunhao Zhang; Lin Fu; Yuhang Gong; Ya Hu; Yungang Cao (Natural Hazards, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Differences in root surface adsorption, root uptake, subcellular distribution, and chemical forms of Cd between low- and high-Cd-accumulating wheat cultivars - Ya-Tao Xiao; Zhen-Jie Du; Carlos-A Busso; Xue-Bin Qi; Hai-Qing Wu; Wei Guo; Da-Fu Wu (Environmental Science and Pollution Research, 2020)

Changes in cultivated land patterns and driving forces in the Three Gorges Reservoir area, China, from 1992 to 2015 - Yu-xin Zhang; Yu-kuan Wang; Bin Fu; Ming Li; Ya-feng Lu; Amod Mani Dixit; Suresh Chaudhary; Shan Wang (Journal of Mountain Science, 2020)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Application of computed tomography in the analysis of glass beads unearthed in Shanpula cemetery (Khotan), Xinjiang Uyghur Autonomous Region - Qian Cheng; Xueyan Zhang; Jinlong Guo; Bo Wang; Yong Lei; Guangzhao Zhou; Ya’nan Fu (Archaeological and Anthropological Sciences, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Study on synthesis and biological effects of a series of 3,4-dihydroisoquinoline-2(1H)-carboxamide derivatives - Zhi-Yang Fu; Qing-Hao Jin; Ya-Nan Xia; Hai-Ying Jiang; Li-Ping Guan (Medicinal Chemistry Research, 2019)

Silencing of GbANS reduces cotton resistance to Verticillium dahliae through decreased ROS scavenging during the pathogen invasion process - Lu Long; Jing-Ruo Zhao; Fu-Chun Xu; Wen-Wen Yang; Peng Liao; Ya Gao; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Controlling factors of soil selenium distribution in a watershed in Se-enriched and longevity region of South China - Ya Shao; Chongfa Cai; Haitao Zhang; Wei Fu; Xuemei Zhong; Shen Tang (Environmental Science and Pollution Research, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Agricultural opportunity costs assessment based on planting suitability: a case study in a mountain county in southwest China - Ju Liu; Bin Fu; Yu-kuan Wang; Ya-feng Lu; Pei Xu (Journal of Mountain Science, 2017)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

Deletion of a target gene in Indica rice via CRISPR/Cas9 - Ying Wang; Lizhao Geng; Menglong Yuan; Juan Wei; Chen Jin; Min Li; Kun Yu; Ya Zhang; Huaibing Jin; Eric Wang; Zhijian Chai; Xiangdong Fu; et al. (Plant Cell Reports, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Perfluoroalkyl substances with isomer analysis in umbilical cord serum in China - Ya-Zhi Zhang; Xiao-Wen Zeng; Zhengmin Qian; Michael G. Vaughn; Sarah Dee Geiger; Li-Wen Hu; Long Lu; Chuanxi Fu; Guang-Hui Dong (Environmental Science and Pollution Research, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Effects of area size, heterogeneity, isolation, and disturbances on urban park avifauna in a highly populated tropical city - Hsiang-Yi Chang; Ya-Fu Lee (Urban Ecosystems, 2016)

Baseline sensitivity and control efficacy of fluazinam against Sclerotinia sclerotiorum - Hong-Jie Liang; Ya-Li Di; Jin-Li Li; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Baseline sensitivity and control efficacy of DMI fungicide epoxiconazole against Sclerotinia sclerotiorum - Jin-Li Li; Xiang-Yang Liu; Ya-Li Di; Hong-Jie Liang; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Intraneuronal accumulation of Aβ42 induces age-dependent slowing of neuronal transmission in Drosophila - Jing-Ya Lin; Wen-An Wang; Xiao Zhang; Hai-Yan Liu; Xiao-Liang Zhao; Fu-De Huang (Neuroscience Bulletin, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of the proteins in green cotton fiber using a proteomics-based approach - Yan-Jun Li; Fu-Xin Wang; Ya-Qin Wang; Yong-Chang Liu; Xin-Yu Zhang; Yu-Qiang Sun; Jie Sun (Biotechnology Letters, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Defects in cytoskeletal microtubule deployment of microsporocytes contribute to fertility loss in genic male-sterile Chinese cabbage - Shao Fu; Ya Nan Zhang; Ya Ying Wang; Xue Yi Zhu; Hui Qiao Tian; Scott D. Russell (Plant Reproduction, 2013)

Preparation and evaluation of a new releasable PEGylated tumor necrosis factor-α (TNF-α) conjugate for therapeutic application - ChuanYun Dai; Ya Fu; ShaoCheng Chen; Biao Li; Bo Yao; WanHong Liu; LiQing Zhu; Nan Chen; Ji Chen; Qiang Zhang (Science China Life Sciences, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

Diallyl disulfide induces Ca2+ mobilization in human colon cancer cell line SW480 - Chung-Yi Chen; Chien-Fu Huang; Ya-Ting Tseng; Soong-Yu Kuo (Archives of Toxicology, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Laticiferous canal formation in fruits of Decaisnea fargesii: a programmed cell death process? - Ya-Fu Zhou; Wen-Zhe Liu (Protoplasma, 2011)

PTOV1 is associated with UCH-L1 and in response to estrogen stimuli during the mouse oocyte development - Yu-Wei Yao; Yan Shi; Zhe-Fu Jia; Ya-Hong Jiang; Zheng Gu; Jian Wang; Mohamad Aljofan; Zhao-Gui Sun (Histochemistry and Cell Biology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Linkage with cathepsin B-sensitive dipeptide promotes the in vitro and in vivo anticancer activity of PEGylated tumor necrosis factor-alpha (TNF-α) against murine fibrosarcoma - ChuanYun Dai; Ya Fu; Biao Li; YiGuang Wang; Xuan Zhang; JianCheng Wang; Qiang Zhang (Science China Life Sciences, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Prostasin inhibits cell invasion in human choriocarcinomal JEG-3 cells - Xiao-jie Ma; Ya-yuan Fu; Yu-xia Li; Li-mei Chen; Karl Chai; Yan-ling Wang (Histochemistry and Cell Biology, 2009)

Bats aloft: variability in echolocation call structure at high altitudes - Erin H. Gillam; Gary F. McCracken; John K. Westbrook; Ya-Fu Lee; Michael L. Jensen; Ben B. Balsley (Behavioral Ecology and Sociobiology, 2009)

Sequence Polymorphism and Evolution of Three Cetacean MHC Genes - Shi Xia Xu; Wen Hua Ren; Shu Zhen Li; Fu Wen Wei; Kai Ya Zhou; Guang Yang (Journal of Molecular Evolution, 2009)

A High Polymorphism Level in Rhinopithecus roxellana - Deng Pan; Hong-Xing Hu; Shi-Jie Meng; Zheng-Ming Men; Yun-Xin Fu; Ya-Ping Zhang (International Journal of Primatology, 2009)

Somatic Embryogenesis and in vitro Flowering in Saposhnikovia divaricata - Qi Qiao; Fu-Wu Xing; Ya-Ping Xiao; Hong-Feng Chen (Journal of Plant Growth Regulation, 2009)

Development of 15 polymorphic microsatellite loci from Garrulax morrisonianus (Timaliidae), an endemic avian species of Taiwan - Tzen-Yuh Chiang; Sao-Cheng Lao; Ya-Fu Lee; Cheng-Te Yao (Conservation Genetics, 2008)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Iridovirus Bcl-2 protein inhibits apoptosis in the early stage of viral infection - Pei-Wen Lin; Yi-Jen Huang; Joseph Abraham Christopher John; Ya-Nan Chang; Chung-Hsiang Yuan; Wen-Ya Chen; Chiao-Hwa Yeh; San-Tai Shen; Fu-Pang Lin; Wen-Huei Tsui; Chi-Yao Chang (Apoptosis, 2008)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Mitochondrial Control Region and Population Genetic Patterns of Nycticebus bengalensis and N. pygmaeus - Deng Pan; Jing-Hua Chen; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Xiangyu Jinggong; Vu Ngoc Thanh; Oliver Ryder; Leona Chemnick; Hong-Wei Zhang; et al. (International Journal of Primatology, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

Molecular Phylogeny of Nycticebus Inferred from Mitochondrial Genes - Jing-Hua Chen; Deng Pan; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Vu Ngoc Thanh; Oliver Ryder; Hong-Wei Zhang; Yun-xin Fu; Ya-ping Zhang (International Journal of Primatology, 2006)

Specific amino acid restriction inhibits attachment and spreading of human melanoma via modulation of the integrin/focal adhesion kinase pathway and actin cytoskeleton remodeling - Ya-Min Fu; Hui Zhang; Mingjie Ding; Yi-Qi Li; Xing Fu; Zu-Xi Yu; Gary G. Meadows (Clinical & Experimental Metastasis, 2005)

Protective effects of adenoviral cardiotrophin-1 gene transfer on rubrospinal neurons after spinal cord injury in adult rats - Zheng-Feng Zhang; Wei-Hong Liao; Qing-Feng Yang; Hong-Yun Li; Ya-Min Wu; Xin-Fu Zhou (Neurotoxicity Research, 2003)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

The Origin and Genetic Diversity of Chinese Native Chicken Breeds - Dong Niu; Yan Fu; Jing Luo; Hui Ruan; Xu-Ping Yu; Gong Chen; Ya-Ping Zhang (Biochemical Genetics, 2002)

Mitochondrial Genetic Variation in Chinese Pigs and Wild Boars - Yong-Fu Huang; Xian-Wei Shi; Ya-Ping Zhang (Biochemical Genetics, 1999)

Inhibition of B16BL6 melanoma invasion by tyrosine and phenylalanine deprivation is associated with decreased secretion of plasminogen activators and increased plasminogen activator inhibitors - Bertha A. Pelayo; Ya-Min Fu; Gary G. Meadows (Clinical & Experimental Metastasis, 1999)

Genetic Diversity of Cattle in South China as Revealed by Blood Protein Electrophoresis - Long Nie; Ying Yu; Xi-Quan Zhang; Guan-Fu Yang; Ji-Kun Wen; Ya-Ping Zhang (Biochemical Genetics, 1999)